2000
DOI: 10.1101/gr.146600
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Evolution: The Junction of Mammalian Chromosomes in the Formation of Mouse Chromosome 10

Abstract: During evolution, chromosomes are rearranged and become fixed into new patterns in new species. The relatively conservative nature of this process supports predictions of the arrangement of ancestral mammalian chromosomes, but the basis for these rearrangements is unknown. Physical mapping of mouse chromosome 10 (MMU 10) previously identified a 380-kb region containing the junction of material represented in human on chromosomes 21 (HSA 21) and 22 (HSA 22) that occurred in the evolutionary lineage of the mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
(27 reference statements)
1
16
0
Order By: Relevance
“…This difference was mainly accounted for by a lower fraction of repetitive elements in the mouse. Human unique sequence represented 1.04 Mb, versus 0.97 Mb in the mouse, consistent with the results in several other studies (Martindale et al 2000;Pletcher et al 2000). The relative paucity of repeats in the mouse genome might be explained in part by reduced transposition activity of repetitive elements in rodents (Casavant et al 2000).…”
Section: Discussionsupporting
confidence: 85%
“…This difference was mainly accounted for by a lower fraction of repetitive elements in the mouse. Human unique sequence represented 1.04 Mb, versus 0.97 Mb in the mouse, consistent with the results in several other studies (Martindale et al 2000;Pletcher et al 2000). The relative paucity of repeats in the mouse genome might be explained in part by reduced transposition activity of repetitive elements in rodents (Casavant et al 2000).…”
Section: Discussionsupporting
confidence: 85%
“…Human SGLT3 was the first SGLT to be described as a sensor and not a transporter after extracellular glc resulted in cell depolarization without glc transport (4). While in humans there is only one gene that codes for one SGLT3 protein, in mouse (26) and rat there are two genes coding for the proteins SGLT3a and SGLT3b. The amino acid identities between hSGLT3 and mSGLT3a, and, between hSGLT3 and mSGLT3b, are 80% and 77%, respectively, while mSGLT3a and mSGLT3b are 75% identical.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse, both genes, Slc5a4a and Slc5a4b, which code for mouse SGLT3a (mSGLT3a, gene ID: 64452) and mouse SGLT3b (mSGLT3b, gene ID: 64454), respectively, are found on chromosome 10 (26). In rat, these two genes are located on chromosome 20 (gene ID for rat type 3a: 294341 and for rat type 3b: 294342).…”
mentioning
confidence: 99%
“…Studies by Puttagunta et al (2000) and Pletcher et al (2000) on evolutionary breakpoints in mouse chromosome 10 showed an association with a region of very high (60%-70%) repeated sequence content and Dehal et al (2001) found a concentration of LINEs and LTR elements at evolutionary breakpoints. Consideration of the gross distribution of repeated elements, including simple repeats, and base composition in segment 5 (the breakpoint region) as a whole compared with the rest of the Del36H sequence, showed no apparent associations.…”
Section: Sites Of Evolutionary Rearrangementmentioning
confidence: 96%